2018
DOI: 10.18295/squmj.2017.17.04.011
|View full text |Cite|
|
Sign up to set email alerts
|

Diabetes-Related Knowledge and Preventative Practices Among Government Employees with Diabetes in Kuwait

Abstract: Objectives: Diabetes mellitus (DM)-related knowledge and preventative practices are vital for the successful management of this condition. In Kuwait, few studies have been conducted to evaluate the knowledge and preventative practices of DM patients. This study aimed to assess DM-related knowledge and preventative practices among government employees with DM in Kuwait and to examine associations between DM knowledge, preventative practices and other variables. Methods: This cross-sectional study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The reported unhealthy diet in Emirati women was also reflected in the unfavourably high BMI values extracted from the participants' medical records: 29% of participants were overweight, and as much as 67% were obese, a troubling observation. The BMI values of the Emirati participants were even higher than those previously reported from the same clinic [114,216], and neighbouring Gulf countries [246,247]. As mentioned previously in the Introduction, T2DM associated with obesity is a major public health concern, and in many patient groups similar to our participants, these conditions have reached an almost epidemic order of magnitude [8,9,248].…”
Section: Lifestyle Managementsupporting
confidence: 45%
“…The reported unhealthy diet in Emirati women was also reflected in the unfavourably high BMI values extracted from the participants' medical records: 29% of participants were overweight, and as much as 67% were obese, a troubling observation. The BMI values of the Emirati participants were even higher than those previously reported from the same clinic [114,216], and neighbouring Gulf countries [246,247]. As mentioned previously in the Introduction, T2DM associated with obesity is a major public health concern, and in many patient groups similar to our participants, these conditions have reached an almost epidemic order of magnitude [8,9,248].…”
Section: Lifestyle Managementsupporting
confidence: 45%
“…Studies from both developed and developing countries have reported that diabetes-related knowledge is generally poor among patients with diabetes mellitus [ 21 – 24 ], in line with our study results that showed that knowledge and practice scores of diabetes mellitus management and monitoring were also below average. A recent study in Kuwait revealed a considerable diabetes knowledge gap with only 6% of participants demonstrating high levels of diabetes-related knowledge [ 25 ]. Most of the respondents in our study, knew the drug name of the diabetes medication they were prescribed, however barely 20% were aware of its side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that diet knowledge is a critical factor affecting diet behaviors and food choices. Studies in both developed and developing countries have indicated that knowledge of diabetes is generally low in patients with DM (21,22). Accordingly, designing educational interventions based on nutritional knowledge for diabetics can help complete the stages of changing the nutritional behavior.…”
Section: Discussionmentioning
confidence: 99%